2013
DOI: 10.1016/j.gaceta.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad en el porcentaje de cesáreas y en los motivos para realizarlas en los hospitales españoles

Abstract: Research on non-clinical factors could clarify the differences in the ratio of cesarean sections in private hospitals compared with public hospitals and among distinct levels of public hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The rates of obstetric intervention in full-term single births found in the settings studied show a higher rate of caesarean sections in hospitals with a lower volume of births, which conforms to the internal assessment of the SANC and other studies conducted in Spain [36]. In terms of instrumental births, higher intervention rates can be seen in the group of privately funded hospitals, and within this group the highest level of intervention was observed among those with fewer births.…”
Section: Discussionsupporting
confidence: 86%
“…The rates of obstetric intervention in full-term single births found in the settings studied show a higher rate of caesarean sections in hospitals with a lower volume of births, which conforms to the internal assessment of the SANC and other studies conducted in Spain [36]. In terms of instrumental births, higher intervention rates can be seen in the group of privately funded hospitals, and within this group the highest level of intervention was observed among those with fewer births.…”
Section: Discussionsupporting
confidence: 86%
“…Source: Spanish Ministry of Health. See alsoRedondo et al (2013). In a context of public, universal healthcare, lower rates of c-sections in public hospitals in Spain are consistent with the lower incidence of c-sections among the uninsured in the US(Aron et al, 2000).26 In Spain private hospitals can be privately owned and operated, or privately owned, but dependent on the National Health System.…”
mentioning
confidence: 86%
“…Mothers with private insurance (many public servants who may opt for private healthcare, as well as some affluent families) tend to give birth in private clinics in the absence of birth complications. Guidelines of patient care and average length of hospital stays are similar to the National Health System, but private hospitals show a much higher prevalence of c-sections,as well as births with obstetric intervention (including induction of labor, epidural, forceps, and episiotomy; Redondo et al 2013, Escuriet et al 2014). It's been suggested that the high percentage of cesarean sections without medical indication in private hospitals could be due to their "greater receptivity to women's demands" (Redondo et al 2013).…”
Section: Institutional Framework: the Benefit Cancellationmentioning
confidence: 99%
“…It is interesting the results observed by Rebelo, Redondo and Soto-Vega where CS reaches more than 60% of the deliveries procedures after the 30 years old, reaching 82.5% of women older than 30 in México. 13,14…”
Section: What Is the Age Range Among Women Having Cs?mentioning
confidence: 99%